Religious Preaching through the Method of Mujawwad Tilawah - Mukhlis Aliyudin; Enjang AS; Zaini Hafidh (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2018)
This research departs from the khithabah ta’tsiryah (religious preaching) activity presented by KH. Ujang Hidayat, a preacher who is also the leader of the Asy-Syifa Cicalengka-Bandung Islamic Boarding School. His lecture is unique and distinctive and different from the method commonly used by other preachers. The recitation of the verses of the Qur'an is used as the legal basis of the study or reference in a discussion, recited with special tones or lagham and differs according to the contents of the message contained in the verse of the Qur'an. The purpose of this study is to know and describe the understanding, meaning, and experience of KH. Ujang Hidayat used the recitation method of mujawwad in khithabah ta’tsiriyah in the Majlis Ta'lim As-Sabab. This study uses a qualitative approach to phenomenology study methods. Data collection techniques are carried out by interviews, observation and document study. While the data collection instruments use field notes, cameras and conversation recording devices. While data analysis in the form of unitization of data, categorization, and interpretation of data and validity of data. The results of the study showed that the mujawwad recitation method used by KH. Ujang Hidayat in the khithabah ta’siriyah process in Majlis Taklim As-Sabab was understood as a method of lecture accompanied by rhythms and tones of recitation of the verses of the Qur'an which were adjusted to the contents of the message contained therein. The tilawah mujawwad method is interpreted as a process of delivering the contents of the Qur'an's message, the way of reading is based on the mujahad recitations with slower rhythms of reading and the rhythm of the muratal recitations by adhering to certain tones which are adjusted to qiraat. The use of the tawawah mujawad method can be used in khithabah ta’tsiriyah if the preacher has mastered the ulum al-Qur'an, the interpretation of the Qur'an and qiraa'at sab'ah.Penelitian ini bertolak dari kegiatan khithabah ta’tsiryah (ceramah keagamaan)  yang disampaikan oleh KH. Ujang Hidayat, seorang mubaligh yang menggunakan metode khusus dalam proses tablighnya, yaitu metode tilawah mujawwad. Metode ini dipandang unik dan berbeda dengan metode yang biasa digunakan oleh mubaligh lainnya, terutama dalam pembacaan ayat-ayat al-Qur’an yang digunakan sebagai dasar hukum kajian dalam sebuah pembahasan. Tujuan penelitian ini untuk mengetahui dan mendeskripsikan pemahaman, pemaknaan, dan pengalaman KH. Ujang Hidayat dalam menggunakan metode tilawah mujawwad dalam khithabah ta’tsiriyah di Majlis Ta’lim As-Sabab. Penelitian ini menggunakan jenis penelitian kualitatif dengan metode studi fenomenologi. Teknik Pengumpulan data dilakukan dengan wawancara, observasi dan studi dokumen. Sedangkan instrumen pengumpulan data menggunakan catatan lapangan, kamera dan alat perekam percakapan. Sementara analisis data berupa unitisasi data, kategorisasi dan penafsiran data serta uji abash data. Hasil penelitian menunjukkan bahwa metode tilawah mujawwad yang digunakan oleh KH. Ujang Hidayat dalam proses khithabah ta’siriyah di Majlis Taklim As-Sabab dipahami sebagai metode ceramah yang disertai dengan irama dan nada pembacaan ayat-ayat al-Qur’an yang disesuaikan dengan isi pesan yang terkandung didalamnya. Metode tilawah mujawwad dimaknai sebagai sebuah proses penyampaian isi pesan al-Qur’an yang cara pembacaannya didasarkan pada tilawah mujawaad dengan irama yang lebih lambat dari bacaan dan irama tilawah muratal dengan tetap berpatokan pada nada tertentu yang disesuaikan qiraa’at sab’ah. Penggunaan metode tilawah mujawwad dapat digunakan dalam khithabah ta’tsiriyah apabila mubaligh-nya menguasai ulum al-Qur’an, tafsir al-Qur’an dan qiraa’at sab’ah.